Implementation of Class Management as an Effort towards National Education Goals - Syarifudin, Syarifudin; Iskandar, Muhammad Rozi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Carrying out classroom management is one of the teacher's activities in growing and maintaining an effective classroom organization. So, the teacher in producing an active and effective learning process is by managing the class well. Teachers in managing the class must pay attention to the suitability of the educational levels from Elementary School to High School. Teachers, in carrying out their noble duties, must at least understand the manifestations of classroom management such as curriculum, buildings, facilities, teachers themselves, students, class dynamics and the surrounding environment. These components do not stand alone, but are interrelated and influence each other. Teachers in carrying out their noble duties must at least understand the manifestations of classroom management such as curriculum, buildings, facilities, teachers, students, class dynamics and the surrounding environment. These factors do not stand alone, but are interrelated and influence each other. The important guidelines that must be understood in education, especially educators, are religion, pencasila, UUD 45 which is further explained by the articles in UUD 45. culture, and the goals of national education, which is a formulation of the quality space that society must have. This goal is the most operational source in the development of education in the beloved country of the Republic of Indonesia.